1989
DOI: 10.1007/bf00442002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the behavioral effects of adenosine agonists and dopamine antagonists in mice

Abstract: The adenosine agonists 5'-N-ethylcarboxamideadenosine (NECA), 2-chloroadenosine (2-CLA), N6-cyclohexyladenosine (CHA), N6-cyclopentyladenosine (CPA), 2-(phenylamino)adenosine (CV-1808) and R and S isomers of N6-phenylisopropyladenosine (R-PIA and S-PIA) decreased spontaneous locomotor activity in mice and, except for CPA, did so at doses that did not impair motor coordination, a profile shared by dopamine antagonists. CV-1808, the only agent with higher affinity for A2 as compared with A1 adenosine receptors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…FITC-APEC binding to bovine striatal membranes was saturable, with the estimated K D (57 ± 2 nM) similar to the K i value obtained in competition studies using pmol/mg protein) found by using A 2a -adenosine receptor radioligands [17,25,26] for similarly prepared tissues of various animal species (i.e., bovine, guinea pig, man, mouse, rabbit, and rat). Despite the moderate differences in B max obtained using fluorescent ligand and radioligand binding techniques, FITC-APEC binding was inhibited by compounds that recognize A 2a -adenosine receptors in a competitive manner, while agents that do not interact with A 2a -adenosine receptors did not inhibit FITC-APEC binding (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…FITC-APEC binding to bovine striatal membranes was saturable, with the estimated K D (57 ± 2 nM) similar to the K i value obtained in competition studies using pmol/mg protein) found by using A 2a -adenosine receptor radioligands [17,25,26] for similarly prepared tissues of various animal species (i.e., bovine, guinea pig, man, mouse, rabbit, and rat). Despite the moderate differences in B max obtained using fluorescent ligand and radioligand binding techniques, FITC-APEC binding was inhibited by compounds that recognize A 2a -adenosine receptors in a competitive manner, while agents that do not interact with A 2a -adenosine receptors did not inhibit FITC-APEC binding (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…An association between A 2a -adenosine receptors and the postsynaptic dopaminergic system also has been proposed [17,18]. Moreover, A 2a -adenosine receptor agonists have shown antipsychotic-like effects [17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistent with these previous findings of an interaction between DA and adenosine receptors, adenosine A 2A agonists have been shown to induce effects that resemble those produced by DA antagonists or DA depletions (Heffner et al 1989;Barraco et al 1993;Ferré 1997;Rimondini et al 1997). Administration of the adenosine A 2A receptor agonist CGS 21680 into the ventricles inhibited acquisition and expression of wheel running behavior (Cabeza de Vaca et al 2007).…”
Section: Introductionsupporting
confidence: 84%
“…Nevertheless, we have also demonstrated A 2A -D 2 receptor interactions in the ventral striatum that are similar to interactions in the dorsal striatum (reviewed in Ferré, 1997). At the behavioral level, by acting on the ventral striatum, A 2A receptor agonists counteract and A 2A antagonists potentiate the motor, discriminative and rewarding effects of psychostimulants (Heffner et al, 1989;Popoli et al, 1994;Rimondini et al, 1997;Shimazoe et al, 2000;Knapp et al, 2001;Poleszak and Malec, 2002;Justinova et al, 2003;Filip et al, 2006). The non-selective A 1 and A 2A antagonist caffeine also potentiates these responses to psychostimulants (Misra et al, 1986;Logan et al, 1989;Gauvin et al, 1990;Horger et al, 1991;Comer and Carroll, 1996;Gasior et al, 2000;Munzar et al, 2002).…”
Section: Adenosine a 2a Receptors In The Ventral Striatum And The Acumentioning
confidence: 99%